Understanding Spain and Europe in the Global Digital Sector - Félix Hernández de Rojas; Pilar Rodríguez Pita; Jorge Emiliano Pérez Martínez (International Telecommunications Society (ITS), 2022)
During the following years and, specially, during this first half decade, the UE will have to provide a comprehensive and efficient answer in terms of sets of strategies and politics to build up a healthy and competitive Digital Sector. Some of these principia are currently under development (specifically all related with 2030 Digital Compass) thanks to the largest multimillion public investment ever made, coming from the recovery plan instrument, The NextGeneration Funds. The main objective in our research is to provide a clear and systematic diagnostic and critical analysis around this opportunity, using several methodological qualitative and quantitative tools along the paper. Our research also will try in the medium term, using this systematic approach, to create some methodological framework able to cluster and compare other OCDE countries so it will help them to understand and develop their digital planned policies. All governments boost digitalisation in their countries, however, their policies and their digital economies/sectors are very different. (...)
Keywords: 330